Educational Media for Enhancing Sexual Awareness in Children with Intellectual Disabilities: A Systematic Literature Review and Bibliometric Analysis - Afrina Devi Marti; Marlina Marlina; Mega Iswari Binah Asnah; Elsa Efrina; Afrina Devi Marti; Marlina; Mega Iswari Binah Asnah (Universitas Negeri Malang, 2027)
This study aims to analyze global publication trends and synthesize the mapping of design components, focus, and key findings from studies on the development of educational media based on sexual awareness for children with intellectual disabilities. The study was conducted through a systematic literature review from 2010–2026 using a qualitative descriptive approach with bibliometric and meta-aggregation analyses. The results indicate that only a few studies specifically address the development of educational media for children with intellectual disabilities and sexual awareness. Most studies focus on the use of innovative media such as Augmented Reality (AR), and empirically, learner-centered and play-based approaches have demonstrated higher effectiveness in children’s engagement and learning outcomes. The limitations identified in the reviewed literature indicate that the educational media currently developed generally still rely on broad validation instruments rather than those specifically designed according to children’s developmental stages and socio-cultural contexts. Furthermore, studies have not adequately integrated children’s social-emotional focus and interactive technologies such as immersive AR to support contextual and meaningful understanding. The practical implications of this study highlight the importance of developing educational media that are culturally adaptive, relevant to local contexts, and capable of integrating a learner-centered approach with a developmentally sensitive framework in designing focus components, syntax, and social systems for sexual education media that remain underexplored in previous literature.